Peningkatan kemampuan analisis unsur puisi melalui Discovery Learning dengan pendekatan kontekstual berbantuan video pada siswa Kelas XI-7 SMA N 5 Semarang - Sujiatmi; Imaniar Yordan Christy; Raden Yusuf Sidiq Budiawan (Pascasarjana Universitas PGRI Semarang, 2024)
This research aims to assess the effectiveness of applying the problem-based learning model in improving the ability of students in class Discovery Learning with a contextual approach. It is hoped that this evaluation will provide educators and researchers with deeper insight into the combination of the two approaches. The research was conducted at SMA Negeri 5 Semarang, class XI-7, using the PTK method to improve the ability to analyze elements of poetry through the Discovery Learning learning model with a video-assisted contextual approach. This research used cycle I and cycle II. Each cycle consists of planning, implementation, observation and reflection stages, which are carried out repeatedly to improve actions in the next cycle. The research results show that the application of the Discovery Learning model is effective in improving the ability of class XI-7 students at SMA Negeri 5 Semarang in analyzing the elements of poetry. Students involved in Discovery Learning show increased active participation in group discussions and presentations, which has a positive impact on their understanding of poetry material. The students' average score increased from 88.85 in cycle I to 90.42 in cycle II, indicating that the Discovery Learning model was successful in improving students' ability to analyze the elements of poetry. The suggestion from this research is that teachers need to continue to develop the Discovery Learning model and contextual approach to increase students' participation and understanding in analyzing the elements of poetry. Students must be active in group discussions and presentations to develop critical thinking skills.